E-SERVICES AS CUSTOMER CARE RESOURCE AND MODE OF SERVICE DELIVERY DURING THE EPIDEMIC: A CASE STUDY OF POLOKWANE LOCAL MUNICIPALITY, LIMPOPO PROVINCE - Malahlela M J; Malatji, Thabiso (RADJA PUBLIKA, 2023)
This empirical paper aims to address the impact of electronically rendering services during the pandemic in the South African local government. It is quite evident that the new world of technology usage is amidst us, therefore, calls for an adaptation in customer service and care. It is within the interest of the study that the challenges of e-services are addressed adequately and the setback with e-services is highlighted, which reveals existing institutional capacity prior to the pandemic. The research method that was used in this study is the qualitative method because it uses structured interviews where one provides the explanation physically to the respondent, an explanation that would give a broader understanding of the study. E-services as customer care resources is the use of information technology for delivering government services, this is a way through which services are made available online. Digital transformation of public administration is a way to promote ethical practices and reduce the risks of corruption in local government. E-services as customer care promote efficiency and increase accessibility. In this way, service delivery transforms from traditional administration to electronic communication between the government and citizens. The findings of the study show that the pandemic affected many groups in the community, which required an immediate response from the municipality, as well as a plan to eliminate half of the difficulties encountered during the pandemic. The city has to take a more polished and planned approach. It is suggested that the municipality invest in their employees. Personnel investment is critical to ensure that during a pandemic, no duties overlap or go unfinished due to a lack of workers.